Globalization and development : current trends - Chakrabarti, Shantanu; Chatterjee, Kingshuk; University of Calcutta. Institute of Foreign Policy Studies (Kolkata : Institute of Foreign Policy Studies, Calcutta University ; New Delhi : KW Publishers, 2012)
Papers presented at a conference held at New York City during 18-19 November 2010.
Includes bibliographical references.
Keywords: Globalization -- Economic aspects -- Congresses